KOMPLEKSITAS KEAMANAN ASIA PASIFIK DAN IMPLIKASINYA TERHADAP TRANSFORMASI KOMITMEN PERTAHANAN AMERIKA SERIKAT PASCA PERANG DINGIN - , ALESSANDRO KURNIAWAN ULUNG; , Drs. Dafri Agussalim, MA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
United Statesâs commitment as security guarantor have been begun since Cold War. Nonetheless, the defense commitment is not stagnant because the transformation happens during post Cold War. The transformation means that the United States previously decreased its commitment and then want to increase it two decades later. When spoke up in Australia on November 2011, The President of United States Barack Obama stated that United Statesâs commitment as security guarantor will be strenghtened dan place Asia Pacific as a main focus of United Statesâs military strategy. The increasing of United Statesâs defense commitment is caused by the escalation of enmity level among Asia Pacific states. It can be showed based on three traditional issues, which are Korea Peninsula, South China Sea, and East China Sea. China dan North Korea presents the aggressiveness that succesfully sharpens the enmity relations in the region. Both countries not only threats Asia Pacific states, but also United States as their security guarantor. In order that, United States needs to increase their attendance to deter China and North Korea.